Screening #MeToo : rape culture in Hollywood - Funnell, Lisa, 1980-; Beliveau, Ralph (Albany, NY : SUNY Press, 2022)
Considers how Hollywood films since the 1960s have both reflected and shaped attitudes toward rape and sexual violence.
Introduction: The Promise of #MeToo as a Theoretical Lens -- 1. Delightful Duties? Sexual Violence in the Connery-Era James Bond Films (1962-1971) -- Literary Roots -- Rape as Backstory and Trope -- Myth of Corrective Rape -- Sexual Coercion in Spy Culture -- Post-Craig Era -- 2. Before #MeToo: Maria Schneider and the Cultural Politics of Victimhood -- The Last Tango in Paris Controversy -- Celebrity Agency and the Conditions of Speaking Out -- The Gendered Hierarchies of Fame -- The Cultural Politics of Victimhood -- Conclusion -- Notes -- 3. A Rapist in My Apartment: Class, Rape, and Saturday Night Fever -- Notes -- 4. Deny the Beast: The Howling (1981) and Rape Culture -- 5. A Woman of Obvious Power: Witchcraft and the Case against Marital Rape in 1980s America -- The Foundational Marital Rape Exemption and Its Links to Witchcraft Mythology -- Landmark Marital Rape Case Law in the United States -- "It's Women Who Are the Source": Sex with the Devil in The Witches of Eastwick (1987) -- She Never Looks Dangerous: Renewed Misogyny in The Witches (1990) -- Conclusion -- 6. "The Rapiest Film of the 1980s": Analog "Revenge Porn," Raced and Gendered Surveillance, and Revenge of the Nerds -- Dominant White Male -- Valuable White Female -- Surveillance Technologies, Whiteness, and the Value of the Nonconsensual Image -- The Authenticity and Nonconsent of Surveillance -- Conclusion: Analog "Revenge Porn" -- Notes -- 7. "Nothing happened to her that she didn't invite": Wes Craven, Rape Culture, and the Scream Trilogy -- 8. Survivors in Rape-Revenge Films: Melancholic Vigilantes -- From Historical Narrative to Genre: The Critical Reception of Rape-Revenge Films -- Scape Goats, Doubles, and Mimesis: Trauma in the Rape-Revenge Film -- Capitalism as Mimetic Desire: A Case of Rape -- The Historical Chain of Violence against Women: Trauma, Memory, Affect -- Conclusion -- Notes -- 9. Painting Pain on Her Skin: Vigilante Justice and the Feminist Revenge Heroine in The Girl with the Dragon Tattoo -- Textual Spaces in Fairy Tales and Dragon Tattoos -- The Girl with the Dragon Tattoo on the Big Screen -- Feminist Revenge Heroines before and after #MeToo and #TimesUp -- Notes -- 10. Taking Consent into Account: American Teen Films amidst #MeToo -- Sexual Consent in the #MeToo Era -- Sex in Teen Films before #MeToo -- The Impact of #MeToo on Teen Films -- 11. Flipping the Script on Consent: Recentering Young Women's Sexual Agency in Teen Comedies -- Feminist Re-Presentations in the MeToo Era: Setting the Scene -- The Lives of Young Women On Screen Now -- Teenage Sex After #MeToo
Online resource; title from PDF title page (EBSCO, viewed April 8, 2022).
Includes bibliographical references and index.
JSTOR
Keywords: Motion picture industry -- Social aspects -- California -- Los Angeles -- History; Sex crimes -- California -- Los Angeles -- History; MeToo movement; Cinéma -- Industrie -- Aspect social -- Californie -- Los Angeles -- Histoire; Violence sexuelle -- Californie -- Los Angeles -- Histoire; Mouvement #MoiAussi.; PERFORMING ARTS / Film / History & Criticism; MeToo movement; Motion picture industry -- Social aspects; Sex crimes; California -- Los Angeles; History